The Impact of Family’s Economic on Divorce - Muhammad Firdaus; Zulham Wahyudani; Agustina Agustina (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2022)
Divorce is the breaking of the marriage bond for certain reasons. Economy is on of the reasons husband and wife can demand divorce at the syari’yyah court or the religious court. In the period 2015-2019, the Syari’yyah Langsa Court decided many divorce cases for various reasons, including the economic reason. The purpose of this study was to determine the economic impact of families on divorce in 2015-2019 and to determine the causes that dominated divorce in 2015-2019 at the Syar’iyyah Langsa Court. Researchers conducted research by processing data taken from the Syar’iyyah Langsa Court. The results obtained from this study are base on cases that have been decided by the Syar’iyyah langsa Court in 2015-2019, that the economy has an impact on divorce but the impact is not massive so that the economy does not really affect divorce. The most dominating cause of divorce, which reached 72.8% of the total cases that occurred in 2015-2019 was due to continuous disputes and arguments. Meanwhile, divorces due to economic causes accounted for 9.76% of the total cases that occurred in 2015-2019.